2021
DOI: 10.3390/dairy2040053
|View full text |Cite
|
Sign up to set email alerts
|

Association of Feed Efficiency, Feeding Rate, and Behaviour with the Milk Performance of Dairy Cows

Abstract: Identification of the associations of cow feed efficiency with feeding behaviour and milk production is important for supporting recommendations of strategies that optimise milk yield. The objective of this study was to identify associations between measures of feed efficiency, feed intake, feeding rate, rumination time, feeding time, and milk production using data collected from 26 dairy cows during a 3 month period in 2018. Cows averaged (mean ± standard deviation) 2.2 ± 1.7 lactations, 128 ± 40 days in milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In beef cattle, standing time, standing duration, and feeder visit frequency and duration are significant predictors of RFI (Haskell et al, 2019), and these types of behaviors can be influenced by management factors such as stocking density, feed barrier design, and consistency of feed delivery to name a few (Huzzey et al, 2006;Proudfoot et al, 2009). Feeding rate increases with greater feed competition in lactating cows (Proudfoot et al, 2009), and feeding rate has an inverse relationship with feed conversion ratio (Krpálková et al, 2021). Additionally, interactions exist between nutrient intake and FB, which could be further manipulated.…”
Section: Introductionmentioning
confidence: 99%
“…In beef cattle, standing time, standing duration, and feeder visit frequency and duration are significant predictors of RFI (Haskell et al, 2019), and these types of behaviors can be influenced by management factors such as stocking density, feed barrier design, and consistency of feed delivery to name a few (Huzzey et al, 2006;Proudfoot et al, 2009). Feeding rate increases with greater feed competition in lactating cows (Proudfoot et al, 2009), and feeding rate has an inverse relationship with feed conversion ratio (Krpálková et al, 2021). Additionally, interactions exist between nutrient intake and FB, which could be further manipulated.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported a positive relationship between dry matter intake and milk yield. In Ireland, Krpálková et al (2021) reported the highest milk yield with the highest feed intake in Holstein cows that were kept in individual stalls and received a TMR diet. In their meta-analysis from feeding trials involving Holstein cows conducted in the United States and Canada, Hristov et al (2004) found that stage of lactation improved the prediction of milk yield from nutrient intake.…”
Section: Resultsmentioning
confidence: 99%